LOCAL SEMI AUTOMATIC CLEARING SYSTEM (SOKZ) ON BANK XYZ - Linda Wahyu Widianti; Sahni Damerianta P, SKom., MM Sahni Damerianta P, SKom., MM (Jurnal Sistem Informasi, 1998)
In writing this paper the authors discuss the automatic system that existed at the localclearing of XYZ Bank. This system is used to provide good service to customers thanusing a local automated system which is efficient clearing but did not givesatisfaction in service to customers who have accounts at the bank. Both systemshave advantages and disadvantages of each, but the goal of every bank is to attract thecustomer's money as much as possible while providing good service so that the localclearing system semiotomasi more help service.